Assessment of shear stress related parameters in the carotid bifurcation using mouse-specific FSI simulations. Issue 11 (26th July 2016) - De Wilde, David; Trachet, Bram; Debusschere, Nic; Iannaccone, Francesco; Swillens, Abigail; Degroote, Joris; Vierendeels, Jan; De Meyer, Guido R.Y.; Segers, Patrick
Abstract: The ApoE − / − mouse is a common small animal model to study atherosclerosis, an inflammatory disease of the large and medium sized arteries such as the carotid artery. It is generally accepted that the wall shear stress, induced by the blood flow, plays a key role in the onset of this disease. Wall shear stress, however, is difficult to derive from direct in vivo measurements, particularly in mice. In this study, we integrated in vivo imaging (micro-Computed Tomography-µCT and ultrasound) and fluid–structure interaction (FSI) modeling for the mouse-specific assessment of carotid hemodynamics and wall shear stress. Results were provided for 8 carotid bifurcations of 4 ApoE − / − mice. We demonstrated that accounting for the carotid elasticity leads to more realistic flow waveforms over the complete domain of the model due to volume buffering capacity in systole. The 8 simulated cases showed fairly consistent spatial distribution maps of time-averaged wall shear stress (TAWSS) and relative residence time (RRT). Zones with reduced TAWSS and elevated RRT, potential indicators of atherosclerosis-prone regions, were located mainly at the outer sinus of the external carotid artery. In contrast to human carotid hemodynamics, no flow recirculation could be observed in the carotid bifurcation region.